2008
DOI: 10.1080/03091900600632694
|View full text |Cite
|
Sign up to set email alerts
|

Difference in pulse transit time between populations: a comparison between Caucasian and Chinese children in Australia

Abstract: Pulse wave velocity (PWV) has shown to be a clinically important physiologic measure in the assessment of increased arterial stiffness that is linked to systolic hypertension. Pulse transit time (PTT), which is based on the principle of PWV, has become popular in childhood cardiovascular studies. A previous study has indicated PWV obtained from a Chinese population tends to be higher than that from their Caucasian counterpart of similar age but of different localities. In this study, 67 healthy children (55 Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Whereas, in the majority of the studies this parameter was suggested as a blood pressure surrogate, PTT has gradually become a popular index of arterial stiffness (Kingwell et al 1997;Nichols 2005). Most importantly, pulse transit time has been used as a measure of vascular health and condition across life span (Safar et al 2003;Vaitkevicius et al 1993;Zahedi et al 2007) in different populations (Foo and Lim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in the majority of the studies this parameter was suggested as a blood pressure surrogate, PTT has gradually become a popular index of arterial stiffness (Kingwell et al 1997;Nichols 2005). Most importantly, pulse transit time has been used as a measure of vascular health and condition across life span (Safar et al 2003;Vaitkevicius et al 1993;Zahedi et al 2007) in different populations (Foo and Lim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, until now, AIx and PWV measured at different sites have not been evaluated in Chinese patients with type 2 diabetes and well‐matched controls. Because the differences in arterial stiffness among different ethnic groups have been previously reported,19,20 it is necessary to investigate the associations between diabetes and indices of arterial stiffness in Chinese inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…Van Velzen, et al identified 43 different methods to determine PTT [20] between an ECG R-peak and a PPG signal [21][22][23][24][25]. A PTT for ECG-PPG measurements is called Pulse Arrival Time (PAT).…”
Section: Introductionmentioning
confidence: 99%